Local government autonomy and self-governance – the Polish perspective - Orankiewicz, Agnieszka; Turała, Maciej (Publishing House of Wroclaw University of Economics and Business, 2024)
The article analyses the state of local governance in Poland by illustrating the degree of decentralisation and financial autonomy on the level of communes. To that end, the article approaches the notions of subsidiarity, decentralisation and sub-national governments’ autonomy, outlines the relations between them, and provides an illustration and discussion of these concepts using data on revenues of communes and urban districts in Poland between 1995 and 2020. The analysis was conducted for territorial units divided into five size categories. The results indicate that the decentralisation of public finance, measured by the ratio of sub-national government expenditure to central government expenditure and sub-national government expenditure to GDP, is growing. However, the degree of autonomy of communes is decreasing. Therefore, the question arises of whether it is not a straight path from self-governance derived from the concept of decentralised state to government administration taken from the concept of a deconcentrated state. The ongoing re-centralisation removes the local authorities’ capacity to manage local affairs, turning them into mere administrators and – in part – spectators, bystanders to these processes, and as such is of significance for the management of local development. The analysis of the degree of local government’s autonomy and self-governance offers a historical perspective (1991-2020), carried out for five size categories of communes and offers the capacity of being extended to other levels of sub-national governments in Poland, and also to sub-national governments in other countries.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 71-88